Distribution of Lewis and Secretor polymorphisms and corresponding CA19‐9 antigen expression in a Chinese population. Issue 11 (4th October 2017) - Guo, Meng; Luo, Guopei; Lu, Renquan; Shi, Weizhong; Cheng, He; Lu, Yu; Jin, Kaizhou; Yang, Chao; Wang, Zhengshi; Long, Jiang; Xu, Jin; Ni, Quanxing; et al.
Abstract : The Lewis ( FUT3 ) and Secretor ( FUT2 ) genes, corresponding to secretion of Lewis ABO (H) histo‐blood group antigen CA19‐9, are highly polymorphic with differences between populations. In this study, the FUT3 and FUT2 genes in 316 Chinese participants were sequenced to detect polymorphisms, and the associated CA19‐9 antigen secretion was also measured. In total, 14 genotypes of FUT3 and 10 genotypes of FUT2 were verified. Le / Le, Le / le 59, 508 and Le / le 59 were the main genotypes of FUT3 with frequencies of 53.2%, 10.7% and 3.5%, respectively. Se / Se, Se / se 385 and se 385 / se 385 were the main genotypes of FUT2, with frequencies of 21.4%, 18.6% and 16.2%, respectively. The alleles le 1067 and le 508 were found extensively in the Chinese population, and the frequency of allele se 385 was shown to be higher than previously reported. Phenotype analysis revealed that 9.8% of individuals were the Lewis‐negative type and 22.5% were the secretor‐negative type. Combined phenotypes showed that 3.2% of participants were of 'double‐negative' phenotype (le, se) and 19.3% were of single dominant non‐secretor phenotype (Le, se). Serum Lewis antigen CA19‐9 levels were significantly different between subgroups and consistent with the defined phenotype. Our study revealed the unique distribution of Lewis and Secretor polymorphisms in a large Chinese population, and decoded the combined genotypes of the two CA19‐9‐related genes. Abstract : The Lewis ( FUT3 ) and Secretor ( FUT2 ) genes, which encode key enzymes in the synthesis of Lewis ABO (H) histo‐blood group antigens, are highly polymorphic. We sequenced the FUT3 and FUT2 genes in 316 Chinese participants. FUT3 ( Le / Le, Le / le and le / le ) and FUT2 ( Se / Se, Se / se and se / se ) genotypes were distinguished. Phenotype analysis revealed that 9.8% of individuals were the Lewis‐negative type and 22.5% were the secretor‐negative type. The combined phenotype analysis showed that 3.2% of participants were 'double‐negative' (le, se) and 19.3% were single dominant non‐secretors (Le, se). Serum Lewis antigen CA19‐9 levels were significantly different between genotypes, and consistent with the defined phenotypes.